Tragedy and hope a history of the world in our time - Quigley, Carroll (GSG & Associates, 1966)
TRAGEDY AND HOPE shows the years 1895-1950 as a period of transition from the world dominated by Europe in the nineteenth century to the world of three blocs in the twentieth century. With clarity, perspective, and cumulative impact, Professor Quigley examines the nature of that transition through two world wars and a worldwide economic depression. As an interpretative historian, he tries to show each event in the full complexity of its historical context. The result is a unique work, notable in several ways. It gives a picture of the world in terms of the influence of different cultures and outlooks upon each other; it shows, more completely than in any similar work, the influence of science and technology on human life; and it explains, with unprecedented clarity, how the intricate financial and commercial patterns of the West prior to 1914 influenced the development of today's world.